La visibilità on-line delle imprese alberghiere: un possibile modello di misurazione - Cioppi, Marco; Curina, Ilaria; Forlani, Fabio; Pencarelli, Tonino (Piccola Impresa / Small Business, 2016)
In a tourist scenario profoundly transformed by the advent of new online players, hotel companies are called today to exploit the online communication tools in a more and more conscious way. In this context, for hotel SMEs, it becomes fundamental to achieve a correct perception of the online presence in order to intervene in real time with specific web marketing actions. The research objectives are 1) to explore the firms’ online presence through an economic literature review 2) to define an online visibility measurement indicator. The research has provided for three sequential phases: 1) the economic literature analysis (to explore the online presence issue/ its principal dimensions) 2) creation of an Index of Online Visibility of Hotel 3) test through three successive measurements of the online visibility of all 227 Hotels of Cattolica. The research has produced three mutually coherent online visibility charts, showing, albeit with some limitations, the validity of the Index.